2015
DOI: 10.1080/10255842.2015.1128530
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modelling of the common carotid artery in the elderly with physiological intimal thickening using layer-specific stress-released geometries and nonlinear elastic properties

Abstract: To investigate the mechanical effects of tissue responses, such as remodelling, in the arteries of the elderly, it is important to evaluate stress in the intimal layer. In this study, we investigated a novel technique to evaluate the effect of layer-specific characteristics on stress in the arterial wall in an elderly subject. We used finite element analysis of a segment of carotid artery with intimal thickening, incorporating stress-released geometries and the stress-strain relationships for three separate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…8 Initially, arteries may dilate in adaptive response to intima–media thickening in order to preserve luminal area, 41 and it has been recently suggested that intimal stress is influenced significantly by location-dependent intimal remodeling. 42 However, these forces influence the initiation of atherosclerotic lesions, which will develop at arterial regions that are exposed to complex blood flow. 8 A deeper understanding of these interactions is essential for the prevention of atheromatous plaque development, its stabilization, and its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…8 Initially, arteries may dilate in adaptive response to intima–media thickening in order to preserve luminal area, 41 and it has been recently suggested that intimal stress is influenced significantly by location-dependent intimal remodeling. 42 However, these forces influence the initiation of atherosclerotic lesions, which will develop at arterial regions that are exposed to complex blood flow. 8 A deeper understanding of these interactions is essential for the prevention of atheromatous plaque development, its stabilization, and its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Following this logic, researchers rationally choose linear models that provide better convergence and speed of computer calculations, while focusing on detailing other aspects of their studies. On the other hand, the strategy of using nonlinear models in the analysis of the work of blood vessels or the heart is also actively presented, despite similar obtained stress amplitudes [29][30][31][32][33][34][35]. Some authors, trending towards the position of complicating material models, argue this by the possibility of obtaining more accurate results [36], however, of course, the final choice between linear and nonlinear description in their studies is shared with the scientific teams themselves.…”
Section: Discussionmentioning
confidence: 99%
“…At higher blood pressure, it stiffened sharply due to the engagement of collagen fibers in load bearing. The difference between the simulation and experiment could be attributed to the forced separation of the media layer from adventitia/intima layers [37]. [28] Cylinder (axisym.)…”
Section: Macro-mechanical Modelingmentioning
confidence: 91%
“…3 Isotropic Sommer and Holzapfel [35] Cylinder (axisym.) 2 Isotropic or Orthotropic Kural et al [36] 3D (FSI) 1 Transversely isotropic Monir et al [37] Ring-like FE model 3 Isotropic…”
Section: Macro-mechanical Modelingmentioning
confidence: 99%